Collaborative Innovation in Labor Market Inclusion. (4th April 2021) - Lindsay, Colin; Pearson, Sarah; Batty, Elaine; Cullen, Anne Marie; Eadson, Will
Abstract: This article deploys the concept of "collaborative innovation" to discuss key stakeholders' and service users' experiences of innovative labor market inclusion services. We draw on work by Sørensen and Torfing (2011, 2016, 2017) to frame collaborative innovation as a distinctive approach to the coproduction of services that respond to user needs, and highlight the importance of governance and leadership practices that foster mutual learning and boundary spanning innovation. The article reports on 102 interviews with service users (in this case, unemployed lone parents) and 117 interviews with key stakeholders involved in local partnerships. We identify benefits from such collaborative approaches in terms of innovative service design and positive outcomes for service users. We conclude that policy makers should consider the potential added value of collaborative innovation in labor market inclusion .